فاعلية نموذج أبعاد التعلم لمارزانو في تنمية التحصيل بمادة الرياضيات لدى طالبات الصف التاسع بمدينة مصراتة (Journal of Academic Research, 2026)
The aim of the current research is to determine the effectiveness of Marzano’s Dimensions of Learning model in developing achievement in the mathematics curriculum for ninth-grade students in Misrata. The research problem was defined in the following main question: What is the effectiveness of using the Dimensions of Learning model in developing achievement among ninth-grade female students in the basic education stage in mathematics?To achieve the research objective, the researcher adopted the experimental method with a quasi-experimental design with its two groups: (experimental and control). To reach the research results, the unit “Finding the Expansion and Algebraic Analysis” was selected from the mathematics curriculum in the first semester of the year 2024-2025 AD. The teacher’s guide and activity book were prepared according to Marzano’s Dimensions of Learning model. An achievement test was also prepared in the experimental unit.The psychometric parameters were verified, and the research sample was selected from two primary schools in the Misrata Education District. The sample consisted of 60 female students, divided into two groups: an experimental group and a control group. The experimental group comprised 30 students, and the control group also comprised 30 students. Equivalence between the two groups in pre-test achievement and intelligence was verified. The data were processed using the Statistical Package for the Social Sciences (SPSS) version 27. The research concluded that the experimental group outperformed the control group in the post-test achievement test and also outperformed the pre-test achievement test. The study concluded with several recommendations, the most prominent of which are:Training courses were held for mathematics teachers on the use of Marzano’s Dimensions of Learning model to achieve the goals of teaching mathematics at different educational stages, and the content of mathematics books was reconsidered to facilitate the use of Marzano’s Dimensions of Learning model in teaching mathematics.